LOW – ALLOY STEEL MELTING TECHNOLOGY - Kenjaboev Shukurjon Sharipovich; Sarimsakova Sokhibakhon Rakhmonjanovna (Scholars Digest Publishing, 2024)
In this article, the mode of liquefaction of steel alloy was used. The obtained liquid metal is cleaned from non – metallic inclusions and gas pores by non – furnace processing, and casting technology was developed on the basis of energy and resource efficient innovative technologies. The composition of the sand – clay mold was worked out to obtain a high – quality cast product, and a high – quality cast product was obtained by liquefaction. Also, thermal treatment regimes were developed to increase the mechanical properties of the cast alloy, and as a result, a high – quality and resource – efficient cast product was obtained.
Keywords: Chrome, manganese, alloyed, shaft, sand – clay mold, hardness.